Microstructural development of cobalt ferrite ceramics and its influence on magnetic properties - Kim, Gi-Yeop; Jeon, Jae-Ho; Kim, Myong-Ho; Suvorov, Danilo; Choi, Si-Young (Metals and materials international, 2013)
The microstructural evolution and its influence on magnetic properties in cobalt ferrite were investigated. The cobalt ferrite powders were prepared via a solid-state reaction route and then sintered at 1200 °C for 1, 2, and 16 h in air. The microstructures from sintered samples represented a bimodal distribution of grain size, which is associated with abnormal grain growth behavior. And thus, with increasing sintering time, the number and size of abnormal grains accordingly increased but the matrix grains were frozen with stagnant grain growth. In the sample sintered for 16 h, all of the matrix grains were consumed and the abnormal grains consequently impinged on each other. With the appearance of abnormal grains, the magnetic coercivity significantly decreased from 586.3 Oe (1 h sintered sample) to 168.3 Oe (16 h sintered sample). This is due to the magnetization in abnormal grains being easily flipped. In order to achieve high magnetic coercivity of cobalt ferrite, it is thus imperative to fabricate the fine and homogeneous microstructure.